Protective effects of (1-(4-hydroxy-phenyl)-3-m-tolyl-propenone chalcone in indomethacin-induced gastric erosive damage in rats - Dhiyaaldeen, S.M.; Amin, Z.A.; Darvish, P.H.; Mustafa, I.F.; Jamil, M.M.; Rouhollahi, E.; Abdulla, M.A. (Biomed Central Ltd, 2014)
Background: Non-steroidal anti-inflammatory drugs (NSAIDs) can result in peptic ulcer disease (PUD) which is a common condition worldwide. The aim of this study was to evaluate the antiulcer properties of (1-(4-hydroxyphenyl)- 3-m-tolyl-propenone) (HPTP) chalcone in rats using indomethacin as ulcerogenic agent. Results: None of the rats showed symptoms of kidney and liver toxicity during the term of the study. Administration of HPTP had decreased the acidity, increased gastric wall mucus and flattening of gastric mucosa and reducing erosive gastric damage area. HPTP also showed dose dependent increase in SOD, GPx activity and PGE(2) level and decrease MDA. H & E stain showed decreased infiltration of leucocytes with edema of submucosal layer. PAS staining showed intense uptake of magenta color of gastric wall mucus in rats fed with HPTP, and immunohistochemical staining of gastric mucosa revealed over-expression of HSP70 protein, down-expression of Bax protein and over expression of TGF-beta in rats administered with HPTP. Conclusion: This study has revealed that chalcone1-(4-hydroxy-phenyl)-3-m-tolyl-propenone can serve as a safe and effective antiulcer agent as it has been proved to increase pH and gastric wall mucus, increase GPx, SOD, PGE(2), and decrease MDA level, ultimately, it has also contributes towards the over-expression of HSP protein andTGF-beta, and down-expression of Bax protein.